Art therapy: Perspectives of South African psychologists - Gower, James A. (My University, 2008)
Art therapy is a method that has a long global history as a treatment alternative when conventional verbal psychotherapy and even pharmacotherapy have failed to facilitate improvement. It helps access, give form to, and integrate experiences, memories, and emotions that cannot be directly verbalised. Art therapy is the creative expression of the client through the use of art making and the subsequent artefacts within therapy. Art therapy is an opportunity for the therapist to access recesses of the client’s mind that may otherwise be hidden. This enables the therapist to utilise these revelations and the artefacts produced strategically within therapy. In South Africa art therapy as a profession does not have a distinct category of its own under the Health Professions Counsel of South Africa (HPCSA), and is not included in psychology training courses at tertiary level. In spite of this, some South African psychologists do use it as a modality in therapy. These psychologists are the subjects of this study. They provided important information regarding the possible uses of art in therapy from a unique South African perspective. The participants in this study have responded each in uniquely favourable terms to questions surrounding the value and benefit of art as a tool of psychological therapy. This unequivocal professional concurrence, while derived from a limited research sample, suggests that art therapy, though severely neglected, holds enormous potential for positive application within the South African context. The interpretations, definitions and applications of art therapy by each of these therapists are admittedly in no way as profound as those evidenced in the international literature examined in the course of this study, yet a vast resource of innovative perspectives, informative considerations along with fresh indicators towards areas for potential future research have come to the fore. According to the participants in this study, art therapy does not receive enough attention in the South African psychological arena. Areas specifically identified by the interviewees in which art therapy can play a role include: group work; preventative work; the crossing of language barriers; providing therapy to the greater population and previously disadvantaged groups; shortening therapy; and trauma work. Art therapy is not limited to age, nor by the presenting problem. It is engaging, and facilitates effective communication. The artefacts produced can serve as historic records of therapy, allowing the therapist and client to recollect the process. Colour can play an important part in therapy, yet the client’s unequivocal personal interpretation of colour should be the focus. Art therapy is not static and facilitates therapeutic movement, client involvement and responsibility. The art activity and artefact provides a concrete rather than verbal medium through which a person can achieve both conscious and unconscious expression and, as such, can be used as a valuable agent for therapeutic change. The image is tangible and serves as constant reminder and anchor to the clients conflict or problem, yet moves it to a safe distance outside the client. Art therapy is implemented in many different ways within South Africa, as is the case internationally. Although a multicultural South African society seems to be different in many contexts, the implementation and occurrence of art therapy appears to be fairly unchanged, and art may be the universal therapeutic language.
Keywords: art therapy; perspectives; South Africa; psychology